Pengetahuan Gizi dan Kesehatan, Keragaman Pangan Serta Aktivitas Fisik Mahasiswa Gizi IPB Selama Masa Pandemi Covid-19: Nutrition and Health Knowledge, Dietary Diversity and Physical Activity of Nutritional Sciences Student in IPB During Covid-19 Pandemic - Syifa, Nisa Hidayatus; Briawan, Dodik; Kustiyah, Lilik (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2022)
Prevention of Covid-19 is a crucial thing to do by everyone, including university students. Implementation of health protocols, eating various foods, and increasing physical activity are among the efforts to prevent and control Covid-19 transmission. This study aimed to analyze the relationship between nutrition and health knowledge with dietary diversity and physical activity among students at IPB University. This cross-sectional study involved 65 subjects. Data collection was carried out using google forms and telephone interviews. The results showed that during the Covid-19 pandemic, most subjects (56.9%) had a moderate knowledge of nutrition and health, and about half of the subjects (49.2%) had a good food diversity with an average consumption was 5.57±1.21 types of food. Most of the subjects (69.2%) had a light physical activity category with an average PAL of 1.49±0.128. There was no significant relationship (p>0.05) between knowledge of nutrition and health with food diversity and physical activity. However, subjects with good nutrition and health knowledge category had a slightly higher average dietary diversity score and physical activity score than those with a lower nutrition and health knowledge category.